The Confirmatory Factor Analysis (CFA) on GST compliance research model in Malaysia - Harun, Zubaidah; Zaki, Pakhriazad Hassan; Ismail, Mohd Hasmadi; Awang, Khairil Wahidin (Imperial Journal of Interdisciplinary Research (IJIR), 2016)
The questionnaire was constructed based on four constructs which are knowledge attitude and communication channels as exogenous variables while GST compliance is endogenous variable. The questionnaires were distributed to the wood-based manufacturers throughout seven states in Peninsular Malaysia. 352 valid data was evaluated for the validity and reliability. The ultimate objective of this article is to acquire the best fit of a research instrument for the GST compliance study using structural equation model (SEM) that enable to taking into account the unreliable factors (items) between exogenous and endogenous constructs. The items of the constructs undergo the confirmatory factor analysis (CFA) procedure involve of unidimensionality test, convergent validity, construct validity and discriminant validity. Followed by the measurement of reliability on all items using Cronbach alpha using SPSS and construct reliability (CR) and average variance extracted (AVE) using AMOS. The result revealed the constructs of the research model achieved the validity and reliability for other further analysis in acquiring high accuracy on the prediction outcomes.